Exercise Intervention Modulates Synaptic Plasticity by Inhibiting Excessive Microglial Activation via Exosomes - Li, Chen; Hu, Jiayi; Liu, Wenhong; Ke, Changkai; Huang, Chuan; Bai, Yifan; Pan, Bingchen; Wang, Junyi; Wan, Chunxiao (Frontiers in Cellular Neuroscience, 2022)
Background—Exosomes can activate microglia to modulate neural activity and synaptic plasticity through phagocytosis of neural spines or synapses. Our previous research found that early four-week exercise intervention in middle cerebral artery occlusion (MCAO) rats can promote the release of exosomes and protect the brain. This study intended to further explore the intrinsic mechanism of neuroprotection by exosome release after exercise. Methods—Rats were randomly divided into four groups: a sham operation (SHAM) group, middle cerebral artery occlusion (MCAO) with sedentary intervention (SED-MCAO) group, MCAO with exercise intervention (EX-MCAO) group, and MCAO with exercise intervention and exosome injection (EX-MCAO-EXO) group. The modified neurological severity score (mNSS), cerebral infarction volume ratio, microglial activation, dendritic complexity, and expression of synaptophysin (Syn) and postsynaptic density protein 95 (PSD-95) were detected after 28 days of intervention. Results—1. Exercise improved body weight and mNSS score, and the survival state of rats after exosome infusion was better. 2. Compared with the SED-MCAO group, the EX-MCAO (P=0.039) and EX-MCAO-EXO groups (P=0.002) had significantly lower cerebral infarct volume ratios (P<0.05), among which the EX-MCAO-EXO group had the lowest (P=0.031). 3. Compared with the SED-MCAO group, the EX-MCAO and EX-MCAO-EXO groups had a significantly decreased number of microglia (P<0.001) and significantly increased process length/cell (P<0.01) and endpoints/cell (P<0.01) values, with the EX-MCAO-EXO group having the lowest number of microglia (P=0.036) and the most significantly increased endpoints/cell value (P=0.027). 4. Compared with the SED-MCAO group, the total number of intersections and branches of the apical and basal dendrites in the EX-MCAO and EX-MCAO-EXO groups was increased significantly (P<0.05), and the increase was more significant in the EX-MCAO-EXO group (P<0.05). 5. The expression levels of Syn and PSD-95 in the EX-MCAO (PSyn=0.043, PPSD-95=0.047) and EX-MCAO-EXO groups were significantly higher than those in the SED-MCAO group (P<0.05), and the expression levels in the EX-MCAO-EXO group were significantly higher than those in the EX-MCAO group (P<0.05). Conclusions—Early exercise intervention after stroke can inhibit the excessive activation of microglia and regulate synaptic plasticity through exosome release.